Effect of Affective Personality Information on Face Processing: Evidence from ERPs - Luo, Qiu L.; Wang, Han L.; Dzhelyova, Milena; Huang, Ping; Mo, Lei (Frontiers in Psychology, 2016)
This study tested the extent to which there are neural correlates of the influence of affective personality information on face processing, using event-related potentials (ERPs). In the learning phase, participants viewed a target individual’s face (with a neutral expression or faint smile) paired with negative, neutral or positive sentences describing the target’s previous typical behavior. In the following EEG testing phase, participants completed gender judgments of the learned faces. Statistical analyses were conducted on measures of neural activity during the gender judgment task. Repeated measures ANOVA of ERP data showed that faces described as having a negative personality elicited larger N170 than did those with a neutral or positive description. The early posterior negativity (EPN) showed the same pattern, with larger amplitudes for faces paired with negative personality than for others. The size of the late positive potential (LPP) was larger for faces paired with positive personality than for those with neutral and negative personality. The current study indicates that affective personality information is associated with an automatic, top-down modulation of face processing.